Bridging Cybersecurity and Enterprise Risk Management in the Digital Era - Agung Setiawan; Ahmad Mufti; Fajli Aijat Mau; Ahmad Purkoni; Agus Setiawan (Pusat Riset dan Inovasi Nasional Mabadi Iqtishad Al Islami, 2025)
This paper explores the strategic integration of cybersecurity into enterprise risk management (ERM) frameworks to enhance digital resilience in modern organizations. Drawing on a qualitative library research method, the study synthesizes literature, models, and case analyses to identify best practices and governance structures that align technical cybersecurity measures with broader organizational goals. The research reveals that treating cybersecurity as an isolated IT function weakens risk visibility and incident response, while embedding it within ERM enables proactive identification, prioritization, and mitigation of cyber risks. The study highlights challenges such as the communication gap between IT teams and senior leadership, lack of standardized cyber-risk metrics, and siloed governance structures. It proposes cross-disciplinary collaboration, integrated risk frameworks (e.g., ISO 31000, NIST), and metrics-driven decision-making as essential components of effective cybersecurity governance. Although conceptual in nature, the findings emphasize the urgent need for cohesive, strategic, and metric-informed approaches to managing cyber threats. Future research should prioritize empirical validation, industry-specific adaptations, and development of standardized cyber-risk indicators to support evidence-based investment and board-level accountability in cybersecurity governance.